Cationized Lignocelluloses as Scavengers for Anionic Surfactants. I. Ionic Interactions - Haïfa Zghida; Robert Gauthier; Ahmed Helal (Adsorption Science & Technology, 2003)
Various cationized lignocelluloses were used for the adsorption of anionic surfactants from wastewaters. The number of cationic sites anchored per g support governed the quantities of pollutant adsorbed. A rapid adsorption led to saturation of all the cationic sites and gave type I adsorption isotherms. Some parameters such as the pH or the temperature had a limited effect. Due to the strong ionic interaction, only partial desorption was observed under severe conditions, viz. when high ionic strength solutions were used at 60–80°C.